2016
DOI: 10.1111/mcn.12350
|View full text |Cite
|
Sign up to set email alerts
|

Individual and structural environmental influences on utilization of iron and folic acid supplementation among pregnant women in Harare, Zimbabwe

Abstract: Micronutrient deficiencies are prevalent among Zimbabweans with serious health and social implications. Due to a lack of a national micronutrient food fortification policy, the Zimbabwe Ministry of Health and Child Care established a policy for the prevention of maternal micronutrient deficiencies, which centres on pregnant women receiving daily iron and folic acid (IFA) at their first antenatal care visit and throughout pregnancy. Despite these efforts, utilization of IFA supplementation in pregnancy in Zimba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…While IFA were in stock during our one-day observations, providers reported that stock outs were frequent [43]. also reported stock outs [43] but other studies have similarly found that demand issues play a larger role than supply issues [42].…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…While IFA were in stock during our one-day observations, providers reported that stock outs were frequent [43]. also reported stock outs [43] but other studies have similarly found that demand issues play a larger role than supply issues [42].…”
Section: Discussionmentioning
confidence: 48%
“…Our results are similar to other studies in India with some notable differences. From an individual level perspective, other studies have found that side effects, bad small and taste, forgetfulness, and limited information about IFA from frontline health workers hinder use [20,31,42]. Prior studies also show that women believe that taking IFA during pregnancy may lead to a large baby, making labor more challenging [8,26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A growing body of literature points to social norms as a critical barrier to IFA uptake 34 35 . Social norms are mores or rules of behavior that are considered acceptable in a group or society 36 .…”
Section: Introductionmentioning
confidence: 99%